2004
DOI: 10.1002/ca.20024
|View full text |Cite
|
Sign up to set email alerts
|

Unusual insertion of the coracobrachialis muscle to the brachial fascia associated with high division of brachial artery

Abstract: Anatomical variations of the coracobrachialis muscle (CBM) are common. We detected an abnormal form of the CBM of the left arm during human cadaver dissection. The CBM originated from the tip of the coracoid process of the scapula and divided into muscular and musculo-aponeurotic bellies. The muscular belly inserted into the middle of the anteromedial surface of the humerus, which is the normal anatomic insertion point of the CBM. The musculo-aponeurotic belly inserted into the medial intermuscular septum as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In our study, there are two heads for coracobrachialis with variable degree of development, that could be attributed to the varied degrees of fusion of its ancestral two heads [ Fig:1]. Ray et al [13] found that CB originated from the coracoid process and then divided into two heads. The muscular head inserted into antero medial part of the middle of humeral shaft while musculo aponeurotic head inserted into medial intermuscular septum forming a tunnel for the passage of superficial brachial artery.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our study, there are two heads for coracobrachialis with variable degree of development, that could be attributed to the varied degrees of fusion of its ancestral two heads [ Fig:1]. Ray et al [13] found that CB originated from the coracoid process and then divided into two heads. The muscular head inserted into antero medial part of the middle of humeral shaft while musculo aponeurotic head inserted into medial intermuscular septum forming a tunnel for the passage of superficial brachial artery.…”
Section: Discussionmentioning
confidence: 72%
“…The lower head is usually suppressed in man, and is sometimes represented by a fibrous band called the "Ligament of Struthers" or "Internal brachial ligament" which extends from supratrochlear spur to medial epicondyle. If this is present, median nerve or brachial artery or both may pass beneath it and might compress them producing vascular spasm or median nerve palsy [6][7][8][9][10][11][12][13][14][15][16][17]. The axillary artery becomes the brachial artery at the lower border of the tendon of the teres major muscle.…”
Section: Introduction Nerve Entrapment In the Osseoaponeurotic Tunnelmentioning
confidence: 99%
“…It is well vascularized and a good choice as a transplant for treating long-standing facial palsy [ 7 ], as a graft for post-mastectomy reconstruction, and in both axillary and infraclavicular deformities [ 7 ]. In some cases, an accessory CB can lead to subcoracoid impingement and nerve palsy of the musculocutaneous, median, or ulnar nerves due to hypertrophy, traumatic injury, or brachial artery compression [ 6 , 8 , 11 - 12 ]. According to Georgiev et al [ 9 ], the absence of clinical reports for neuro-vascular compression due to CB longus can be explained first by the rarity of the variation and, second, by the limited skin incision performed during decompression surgery; therefore, the variation cannot be revealed so it is not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…According to Georgiev et al [ 9 ], the absence of clinical reports for neuro-vascular compression due to CB longus can be explained first by the rarity of the variation and, second, by the limited skin incision performed during decompression surgery; therefore, the variation cannot be revealed so it is not clearly defined. Moreover, variant CB could also cause confusion during surgery and imaging evaluation [ 9 - 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, myofascial expansions, inserting into the muscular fascia, have been described for the temporalis buccinator, coracobrachialis, and semitendinosus and semimembranosus tendons [Ferreira, 1966;Ray et al, 2004;LaPrade et al, 2007;Tuncay et al, 2007].…”
Section: Discussionmentioning
confidence: 99%